Effects of Increasing Salt Concentration for 15 to 22 lb Nursery Pigs - D. Shawk; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. C. Woodworth; H. Williams; A. B. Clark (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 325 maternal line barrows (Line 200 × 400; DNA, Columbus, NE; initially 14.6 lb BW) were used in a 14-d growth trial to determine the optimal inclusion rate of dietary salt for growth performance of nursery pigs weighing approximately 15 to 22 lb. Upon entry of the nursery, pigs were allotted by BW and fed a common starter diet (6 lb/ton added salt and 25% dried whey) for 7 d after weaning. At d 7 after weaning, considered d 0 in the trial, pigs were allotted by pen weight and assigned to 1 of 5 dietary treatments. Treatments included a diet containing 10% dried whey with no added salt, or 4, 8, 12, and 16 lb/ton of added salt. A common Phase 3 diet, containing 7 lb/ton added salt, was then fed from d 14 to d 21. From d 0 to 14, increasing salt increased (linear, P<0.015) ADG and ADFI. Feed efficiency improved (quadratic, P<0.034) as added salt increased from 0 to 12 lb with no further benefits observed thereafter. From d 14 to 21, when pigs were fed a common Phase 3 diet (7 lb/ton added salt), those previously fed no added salt had 20% greater ADG (linear, P<0.013) than those previously fed 4 to 16 lb added salt. The compensatory ADG observed from d 14 to 21 resulted in no overall differences in ADG, ADFI, or F/G from d 0 to 21. In conclusion, it appears that 12 lb/ton of added salt in a diet containing 10% dried whey optimizes ADG, ADFI, and F/G in 15 to 22 lb nursery pigs.
Keywords: chlorine (Cl); sodium (Na); nursery pig; salt